2018
DOI: 10.1039/c8ra07359g
|View full text |Cite
|
Sign up to set email alerts
|

Co-production of fully renewable medium chain α-olefins and bio-oilviahydrothermal liquefaction of biomass containing polyhydroxyalkanoic acid

Abstract: Co-production of fully renewable medium chain α-olefins and bio-oil by hydrothermal liquefaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Applications of mcl-LAO span from "drop-in fuels" to co-monomers in the production of poly-α-olefins (PAO) used as lubricants. 26 Recently, the natural biosynthesis of mcl-LAOs has been elucidated in P. aureginosa. It was discovered that a single gene undA catalyses fatty acid (C 12 ) conversion to 1-undecene.…”
Section: Introductionmentioning
confidence: 99%
“…Applications of mcl-LAO span from "drop-in fuels" to co-monomers in the production of poly-α-olefins (PAO) used as lubricants. 26 Recently, the natural biosynthesis of mcl-LAOs has been elucidated in P. aureginosa. It was discovered that a single gene undA catalyses fatty acid (C 12 ) conversion to 1-undecene.…”
Section: Introductionmentioning
confidence: 99%
“…25 Even though a remarkable amount of the PHB was converted into gaseous propylene, reducing the yield of bio-oil, the gaseous propylene can be easily separated and recovered as a precursor for renewable biofuel 26 or biomaterials. 27 It is clear that PHB is not a good candidate to produce liquid bio-oil. It is possible that PHA produced from longer chain 3-hydroxy fatty acids (e.g., mcl-PHAs) can improve the bio-oil yield via HTL.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We have previously observed that mcl-PHA thermal degradation led 3-OH C10 conversion to 3-decenoic acid via β-elimination. 27 3-decenoic acid was then isomerized into 2decenoic acid, which readily undergoes decarboxylation into 1nonene. There are some side reactions as well to produce small amounts of nonene isomers and decalactones.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations